Why the marginal MRO rate exceeds the ECB policy rate? - Tuomas Välimäki (Bank of Finland, 2006)
In the Eurosystem, banks' interest rate expectations should no longer have resulted in a non-zero tender spread, the difference between marginal and minimum price for liquidity, when the ECB reformed its operational framework for monetary policy implementation in March 2004 so that the policy rates remain constant within reserves maintenance periods.Yet, the tender spread was wider in 2005 than in any single year after 2000, when the ECB switched from fixed to variable rate tenders.Parts of the relevant literature have argued that because of the ECB's asymmetric preferences over deviations of the market rates up and down from the policy rate, the shortest euro interest rates persistently exceed the policy rate This paper argues, however, that when the central bank applies a quantity oriented liquidity policy, a positive tender spread may result from money market inefficiencies and banks' risk aversion even if the central bank preferences are symmetric and the markets do not anticipate any changes in the policy rates.In such a case, the driving force behind the tender spread is banks' uncertainty about their individual allotments at the marginal rate for the Eurosystem main refinancing operations (MROs). Furthermore, the allotment uncertainty is shown to be significantly related to the amount of liquidity supplied in each operation. Hence, the expansion in the MRO volumes experienced since 2002 may have had a major contribution to the emergence and observed growth of the tender spread.
URN:NBN:fi:bof-20140807683
Keywords: D44; E58; 330; main refinancing operations; liquidity; tender spread; allotments